Assessment of heating profiles in model food systems heated by different microwave generators: Solid-state (semiconductor) versus traditional magnetron technology. (July 2020) - Taghian Dinani, Somayeh; Kubbutat, Peter; Kulozik, Ulrich
Abstract: The major challenge of heat processing of foods using the traditional microwave (MW) systems containing magnetron power source is the inhomogeneity of the heating. The aim of this study was to compare a novel solid-state MW system with the traditional magnetron MW system for heat processing of the gellan gel cuboids containing Maillard reaction substrates as model food sample. To evaluate both systems, samples were processed in different positions of turntable in both MW cavities with and without turntable rotation in different levels of absorbed MW power. To investigate the MW heating uniformity, optic fiber temperature sensors were used to determine temperature and were compared with the Maillard reaction induced brown color creation inside the samples. The results show more uniform and homogenous color changes and heating patterns of samples processed in the solid-state MW system compared to those in the magnetron MW system. Highlights: Novel solid-state microwave system was compared with traditional magnetron system. Model food sample was heated in center and north positions of both MW cavities. Effect of turntable activation/inactivation was investigated in both MW cavities. Results show more uniform heat processing in the solid-state MW system. A higher energy absorption efficiency of the solid-state MW system was measured.